Severe androgenetic alopecia as a maker of metabolic syndrome in male patients of androgenetic alopecia: a hospital based case control study - Tilwani, Mohd. R.; Dogra, Naina K.; Dogra, Devraj; Rather, Suhail Raheem; Rather, Parvaiz A. (International Journal of Research in Medical Sciences, 2017)
Background: Several previous studies have investigated the association between androgenetic alopecia (AGA) and metabolic syndrome (MS), with inconsistent results. Objectives of the study were to study the prevalence of metabolic syndrome in male patients of androgenetic alopecia and compare with control population and study the relationship of metabolic syndrome with different grades of AGA. Methods: This prospective hospital based case control study included 100 new clinically diagnosed males of androgenetic alopecia, and age and sex matched control group. Assessment for presence of various components of metabolic syndrome was done following a uniform protocol in cases and controls. AGA was classified as per Hamilton –Narwood classification, grade I to III was classified as mild –moderate and grade IV and higher as severe AGA. Results: Of the 100 male AGA patients (age range 21-50, mean 34.49), 36 had grade II AGA, 24 had grade III AGA, 20 had grade IV AGA, 15 had grade V AGA and 5 had grade VI AGA. Among AGA patients, 60 of patients had mild-moderate AGA and 40 patients had severe AGA. Metabolic syndrome was statistically significantly more common in patients with AGA compared to controls. Among patients of AGA, metabolic syndrome was statistically significantly present in severe AGA compared to mild-moderate AGA. Among the evaluated parameters, like blood pressure, fasting blood sugar, dyslipedemia, abdominal obesity, all were significantly more common in AGA patients compared to controls except abdominal obesity. Conclusions: In the present study, metabolic syndrome was found to be 4.6 times more common in patients of androgenetic alopecia as compared to controls, being statistically significant, and more common in those with severe grades. This suggests that androgenetic alopecia patients especially with severe grades are at risk of metabolic syndrome and other cardiovascular diseases.